2007
DOI: 10.1074/jbc.m705272200
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-derived Growth Factor-induced Stabilization of Cyclooxygenase 2 mRNA in Rat Smooth Muscle Cells Requires the c-Src Family of Protein-tyrosine Kinases

Abstract: Cyclooxygenases (COXs) are crucial rate-limiting enzymes required for the biosynthesis of prostaglandins. COX-2 is an inducible isoform of this enzyme, which is believed to play important roles in the development of atherosclerotic vascular disease. We found that COX-2 expression rapidly increases in response to various signaling events, including activation of the platelet-derived growth factor (PDGF) pathway. Activation of PDGF receptor (PDGFR) in rat aortic vascular smooth muscle cells leads to c-Src-depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 56 publications
3
24
0
Order By: Relevance
“…In this regard, CSE shares the same mechanism as GPCRs for lysophosphatidic acid, bradykinin, and endothelin (13), which promotes the association of Src with proline-rich tyrosine kinase 2, and subsequently the Src/proline-rich tyrosine kinase 2 complex activates the growth factor receptors, such as EGFR and PDGFR (3). Our results were also consistent with the reports showing that activation of EGFR and PDGFR lead to COX-2 expression in various cell types (17,56,57). Gö6976 has been shown to enhance agonist-induced tyrosine phosphorylation of the EGFR, possibly through inhibition of PTP, since a PTP inhibitor, sodium orthovanadate, mimicked the effects of Gö6976 (49).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In this regard, CSE shares the same mechanism as GPCRs for lysophosphatidic acid, bradykinin, and endothelin (13), which promotes the association of Src with proline-rich tyrosine kinase 2, and subsequently the Src/proline-rich tyrosine kinase 2 complex activates the growth factor receptors, such as EGFR and PDGFR (3). Our results were also consistent with the reports showing that activation of EGFR and PDGFR lead to COX-2 expression in various cell types (17,56,57). Gö6976 has been shown to enhance agonist-induced tyrosine phosphorylation of the EGFR, possibly through inhibition of PTP, since a PTP inhibitor, sodium orthovanadate, mimicked the effects of Gö6976 (49).…”
Section: Discussionsupporting
confidence: 94%
“…Recent studies have suggested that numerous components of the PI3K pathway play a crucial role in the expression and activation of inflammatory mediators, inflammatory cell recruitment, immune cell function, airway remodeling, and corticosteroid insensitivity in chronic inflammatory diseases (23). Moreover, several studies have indicated that the expression of COX-2 and synthesis of PGE 2 induced by the proinflammatory mediators are mediated by the activation of PKCs, c-Src, EGFR, PDGFR, or PI3K/Akt in various cell types (24,56,57).…”
mentioning
confidence: 99%
“…61). Intriguingly, the Src family of kinases has recently also been implicated in the stabilization of Ptgs2 mRNA downstream of signaling by platelet-derived growth factor (42). There must also be more than one target of kinase activity.…”
Section: Discussionmentioning
confidence: 99%
“…5) identified multiple mRNA-binding proteins that were preferentially expressed in cMSCs compared with bmMSCs. One of these was CUGbp2, a protein known to stabilize Ptgs2 mRNA (40,41) and whose activity can be regulated by phosphorylation downstream of growth factors (42). We evaluated this gene at both the mRNA and protein level in the context of ERK inhibition and found that although CUGbp2 mRNA was not significantly altered by either serum starvation or by ERK inhibition (Fig.…”
Section: Fgf9 Is Sufficient To Maintain High Levels Of Ptgs2 Expressimentioning
confidence: 99%
“…In our earlier studies we have demonstrated that CELF2 can interact with HuR, a key inducer of RNA stability and translation, and competitively inhibit HuR function (Sureban et al, 2007). Recently, platelet derived growth factor was shown to enhance CELF2 binding to COX-2 mRNA through increased phosphorylation of a tyrosine residue at position 39 in the protein (Xu et al, 2007). These data suggest that posttranscriptional control mechanisms are in place to modulate the CELF2 function as a regulator of stability and translation of AU-rich transcripts.…”
Section: Functionmentioning
confidence: 99%